Personality and motivational systems in mental retardation - Switzky, Harvey N. (International review of research in mental retardation, 2004)
Motivation is the energizing force that drives much of our attention, conscious effort, and achievement in life. Yet this important driving force may be absent, low, or problematic in persons with mental retardation. This special thematic volume in the International Review of Research in Mental Retardation focuses on motivation within this special population. The book explores several theoretical models of motivation, as well as discussing issues of goal orientation, self-regulated academic learning, the setting and monitoring of realistic goals, and social competence for people with mental retardation. Additional chapters discuss the measurement of subjective well-being and quality of life in this population, and strategies for empowering students with developmental difficulties as well as instructional practices and contexts that can enhance motivation, learning, and achievement.